Prefrontal serotonin depletion delays reversal learning and increases theta synchronization of the infralimbic-prelimbic-orbitofrontal prefrontal cortex circuit - Estrada-Reyes, Yoana; Cervantes-Alfaro, José Miguel; López-Vázquez, Miguel Ángel; Olvera-Cortés, María Esther (Frontiers in Pharmacology, 2024)
Prefrontal serotonin plays a role in the expression of flexible behavior during reversal learning tasks since its depletion delays reversal learning. However, the mechanisms by which serotonin modulates the prefrontal cortex during reversal learning remains unclear. Nevertheless, serotonin has been shown to modulate theta activity during spatial learning and memory. Hence, we evaluated the effect of prefrontal serotonin depletion on theta activity in the prefrontal infralimbic, prelimbic, and orbitofrontal (IL, PL, and OFC) subregions of male rats during a spatial reversal learning task in an aquatic T-maze. Prefrontal serotonin depletion delayed spatial reversal learning and led to an increase in theta power in the PL and OFC. Furthermore, animals with serotonin depletion showed an increase in the functional coupling between the OFC and the IL and PL cortices compared with the control group. These results indicate that serotonin regulates reversal learning through modulation of prefrontal theta activity by tuning both the power and functional synchronization of the prefrontal subregions.